Analisis Kesulitan Belajar Berhitung pada Peserta Didik di Kelas Awal SD Negeri 134/I Merbau - Maryati, Eva; Simarmata, Debora Enjelina; Simamora, Martina Grace; Viqri, Denada (Lembaga Yasin AlSys, 2023)
This research tries to show and examine the challenges that children face when learning to count. Classroom observations, tests, and interviews with mathematics students and teachers were part of the research procedures. The findings of the data analysis revealed various problems faced by students, including challenges in understanding and applying basic mathematical principles as well as difficulties in completing direct mathematics tasks. The level of learning challenge is also influenced by various elements including the curriculum, teaching techniques, and the amount of support from the school and family. The consequences of these results include the need for modifications in the way mathematics is taught in the early grades, the creation of more efficient learning methodologies, and joint efforts between schools and parents to help children overcome the challenges of learning to count. This study deepens our awareness of the difficulties students face in laying a strong numeracy foundation and offers insightful suggestions for improving mathematics teaching at the elementary level.